Hadith #3689 - Sunan Abi Dawud - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; ibn Abbas; ibn Umar; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mnswr bin Hyan منصور بن حيان; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
An old man of the people of Wasit narrated from Abu Mansur al-Harith bin Mansur saying: I heard Sufyan Al-Thawri who was asked about al-dadhi. He said: The Messenger of Allah (ﷺ) said: Some of my people will assuredly drink wine calling it by another name.
Grade: Sahih